1993
DOI: 10.1088/0953-2048/6/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a barium deficiency on the structural and magnetic properties of RE Ba2-xCu3Oz(RE=Y, Nd, Eu, Er, Yb)

Abstract: A barium deficiency in the"initia1 composition for the synthesis of high-temperature supercondutors (HTSC), i.e. a nominal (RE Ba,-xCu,O,) composition with 0 $ x $ 1 leads to different materials depending on the nature of the rare earth. If the rare earth is 'yltric' (Y, Er, Yb), the resulting compound is a composite YBa,Cu,O, + Y,BaCuO,, whose critical current density depends on the x-value. The determination of the irreversible behaviour by means of AC susceptibility or magnetization measurements shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…By enhancing the quality of the intergrain contacts, the difference between inter-and intragrain currents vanishes, and the two steps (and peaks) merge (Sauv et al 1993, Planinić et al 1994, Vo et al 1996. However, very small fractions (∼1%) of a poorer quality superconductor or the weak links in single crystals could be detected (Moreira et al 1994, Ren et al 1994 by AC susceptibility.…”
Section: Granularity and Content Of Superconducting Phase (V S )mentioning
confidence: 99%
“…By enhancing the quality of the intergrain contacts, the difference between inter-and intragrain currents vanishes, and the two steps (and peaks) merge (Sauv et al 1993, Planinić et al 1994, Vo et al 1996. However, very small fractions (∼1%) of a poorer quality superconductor or the weak links in single crystals could be detected (Moreira et al 1994, Ren et al 1994 by AC susceptibility.…”
Section: Granularity and Content Of Superconducting Phase (V S )mentioning
confidence: 99%
“…LnBa 2 Cu 3 O y (here Ln = La, Nd, Sm, Eu) has the same structure as YBa 2 Cu 3 O y and also has a high critical temperature that is over 90 K. It is known that Ln ions can easily be substituted for some of the Ba ions. This substitution has been found to bring about characteristic changes, such as a decrease of critical temperature [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Akinaga et al have reported changes of the hole concentration, oxygen content, crystal structure and critical temperature of Sm 1+x Ba 2−x Cu 3 O y (0 ≤ x ≤ 0.4) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…By enhancing the quality of the grain boundaries the two peaks (steps) merge [36], and the magnetic response is ascribed to the sample as a whole.…”
Section: Methodsmentioning
confidence: 99%